Two new Ediacaran small fronds from Mistaken Point, Newfoundland. (13th June 2016) - Mason, Sara J.; Narbonne, Guy M.
Abstract: Small, stemmed frond fossils are common in Ediacaran-aged strata (ca. 565Ma) at Mistaken Point, Newfoundland, and many of them have previously been informally referred to as 'dusters, ' but due to their small size and consequent relatively poor preservation, they have not yet been described taxonomically. Two new genera are herein defined on the basis of their unique constructions: the mop-like rangeomorph Plumeropriscum hofmanni new genus new species, and a flabellate, lobate frond Broccoliforma alta new genus new species. Plumeropriscum hofmanni n. gen., n. sp. has a three-dimensional petalodium structure with numerous primary branches attached at the base of the petalodium rather than at a central axis. Broccoliforma alta n. gen., n. sp. lacks visible branching, and instead has a lobate morphology with a petalodium that is at least superficially similar to the ivesheadiomorph Blackbrookia . Several other previously described taxa had also been included under the umbrella of 'dusters.' Collectively, these taxa show that the low epibenthic tier that small fronds occupied was more diverse than previously realized, with multiple taxa converging on the stemmed, small-frond body plan.